2011
DOI: 10.1111/j.1439-0272.2011.01206.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical evaluation of sperm chromatin and DNA integrity in couples with unexplained recurrent spontaneous abortions

Abstract: The aim of this study was to examine the possible relationship between sperm DNA integrity and chromatin packaging evaluated by cytochemical assays, traditional sperm parameters and recurrent spontaneous abortion (RSA) of unknown origin. In this cohort study, 40 couples with a history of RSA and 40 couples with proven fertility were considered as case and control groups respectively. The semen samples of all husbands were analysed for sperm parameters and also sperm chromatin and DNA integrity assessed using c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 57 publications
2
60
0
4
Order By: Relevance
“…In contrast, some of the recent studies did not agree with this finding. Talebi et al [7] and Brahem et al [16] have provided evidence of an association between sperm motility and recurrent pregnancy loss. In addition, two studies carried out respectively by Absalan et al [8] and Gil-Villa et al [17] have also shown significantly lower sperm motility and normal morphology percentage in men with RPL history.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, some of the recent studies did not agree with this finding. Talebi et al [7] and Brahem et al [16] have provided evidence of an association between sperm motility and recurrent pregnancy loss. In addition, two studies carried out respectively by Absalan et al [8] and Gil-Villa et al [17] have also shown significantly lower sperm motility and normal morphology percentage in men with RPL history.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, an increasing amount of studies have found an important role of sperm chromatin assessment employing different methods in RPL [17,19]. Talebi et al [7] used four different cytochemical tests including aniline blue (AB), chromomycin A3 (CMA3), toluidine blue (TB), acridine orange (AO), as well as nuclear chromatin stability assay, to analyze sperm. They concluded that there was significant correlation between DNA fragmentation and RPL, in agreement with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Доказано, что аномальная (недостаточная) конденсация хроматина вызывает за-держку первого цикла клеточных делений и в дальней-шем повреждение эмбриона [23,24]. Эти повреждения могут приводить к неудачам вспомогательных репро-дуктивных технологий (ВРТ) [25], к потере беремен-ности на ранних сроках [26,27].…”
Section: Objective Study Of the Correlation Between Abnormal Chromatunclassified
“…Эти данные позволяют сделать заключение, что нарушение конденсации хроматина может служить предиктивным показателем аномалий развития эмбри-она как in vivo, так и in vitro. Причем негативные по-следствия нарушения компактизации проявляются в раннее время после оплодотворения [77], приводя к раннему эмбриональному аресту [78] и спонтанным абортам [27,79].…”
Section: корреляционная электронная микроскопияunclassified